Beyond Ability to Pay: Procedural Justice and Offender Compliance With Restitution Orders - Gladfelter, Andrew S. (International journal of offender therapy and comparative criminology, 2018)
Restitution to victims is rarely paid in full. One reason for low rates of payments is that offenders lack financial resources. Beyond ability to pay, however, we argue that fair treatment has implications for offender behavior. This study, a survey of probationers who owed restitution, investigated the links between (a) ability to pay, (b) beliefs about restitution and the criminal justice system, and (c) restitution payment, both the amount paid and number of payments. Results indicate that perceived fair treatment by probation staff—those most directly involved with the collection of restitution payments—was significantly associated with greater payment, net of past payment behavior, intention to pay, and ability to pay. Because restitution has potentially rehabilitative aspects if offenders pay more of the court-ordered amount and if they make regular monthly payments, how fairly probation staff treat probationers has implications for both victims and for the criminal justice system.